Best Answer

34x + 72 is the answer to the equation 12 plus 6x-4 5 plus 2 3x-1.

Q: 12 plus 6x-4 5 plus 2 3x-1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3 - 2 + 6 x 4 = 25

The indefinite integral of (6x4-2)2(24x) dx. The simplest way to do this is to expand the multiplication in the integrand until its a single polynomial comprised of only terms added or subtracted together. (6x4-2)2=(6x4-2)(6x4-2)=36x8-24x4+4=4(9x8-6x4+1) (24x)(4(9x8-6x4+1))=96x(9x8-6x4+1)=96(9x9-6x5+x) From here on out, its simple polynomial antiderivation. The 96 is a constant that can be factored out and ignored. So the antiderivative would be: 96*[9x9/10 - x6 + x2/2] + C

2/12 + 2/12 + 4/12 + 9/12 + 6/12 = 23/12 or 1 and 11/12

2 + 12 + 7 = 21

If 5x plus 3y equals 13, the x equals 2 and y equals 1. This is because 5x2=10 and 3x1=3, and 10+3=13.

Related questions

3 - 2 + 6 x 4 = 25

The indefinite integral of (6x4-2)2(24x) dx. The simplest way to do this is to expand the multiplication in the integrand until its a single polynomial comprised of only terms added or subtracted together. (6x4-2)2=(6x4-2)(6x4-2)=36x8-24x4+4=4(9x8-6x4+1) (24x)(4(9x8-6x4+1))=96x(9x8-6x4+1)=96(9x9-6x5+x) From here on out, its simple polynomial antiderivation. The 96 is a constant that can be factored out and ignored. So the antiderivative would be: 96*[9x9/10 - x6 + x2/2] + C

3x1+2=5

2/12 + 2/12 + 4/12 + 9/12 + 6/12 = 23/12 or 1 and 11/12

If 5x plus 3y equals 13, the x equals 2 and y equals 1. This is because 5x2=10 and 3x1=3, and 10+3=13.

3x=11 x=3+2/3 x²+x=(3+2/3)²+(3+2/3)=17+1/9 so the answer is about 17.11

It is: 12+7+2 = 21

2 + 12 + 7 = 21

The least common multiple or LCM of 6, 8, and 12 would be 24 6x4=24 8x3=24 12x2=24

When it says decreasing powers of x, it just means the exponent (small numbers on the top right corner of x) in decreasing order. Answer: -6x^4 + 3x^2 + 4x + 2

6. 3x1/2=6.

11 + (-5) + (-12) + (-2) =11 - 5 - 12 - 2 =11 - 19 = -8